Porous Graphene Sponge Additives for Lithium Ion Batteries with Excellent Rate Capability - Qian Cheng (Nature Portfolio, 2017)
Abstract Rate capability as well as power performance of lithium ion batteries (LiBs) is becoming more and more important, especially as the application targets of LiBs move from mobile devices to transportation, such as EVs and HEVs. In this research, we report porous graphene sponge additives for both anode and cathode materials for better rate performance. The charge capacity retention improved from 56% to 77% at 6C and from 7% to 45% at 10C with 0.5 wt% added to the anode, while the discharge capacity retention at the 6C rate improved from 43% to 76% and the 10C rate discharge improved from 16% to 40% with the same amount of MG added to the cathode. The cyclability at high rate was also improved with the MG additive. Moreover, preparation of the MG was facile, cost-effective, and compatible with commercially available active materials. These results demonstrate the suitability of MG for use with LiB additives to ensure better rate capability and high rate cyclability.